2020
DOI: 10.3389/fped.2020.00493
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Coronary Artery Lesions in Kawasaki Disease

Abstract: This review summarizes recent advances in understanding the development of coronary arteritis in Kawasaki disease. Kawasaki disease is the most common cause of acquired heart disease among children characterized with coronary artery abnormalities, which can cause myocardial ischemia, infarction, and even death. The pathogenic factors of Kawasaki disease and the pathological process of coronary artery disease are not clear at present, which brings challenges to the prevention and treatment of the disease. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…KD is characterized by systemic medium-sized vascular inflammation, and coronary artery lesions (CALs) are the main complication of KD vasculitis. If there is no timely high-dose intravenous immunoglobulin (IVIG) therapy, CALs could occur in ~30% KD children and bring higher hospitalization costs [ 2 ]. Although the exact molecular mechanism of KD vasculitis still remains obscure, clinical and experimental evidence has shown that KD vasculitis is closely associated with increased vascular permeability that leads to vascular leakiness, decreased plasma proteins, and inflammatory cell infiltration of endothelium [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…KD is characterized by systemic medium-sized vascular inflammation, and coronary artery lesions (CALs) are the main complication of KD vasculitis. If there is no timely high-dose intravenous immunoglobulin (IVIG) therapy, CALs could occur in ~30% KD children and bring higher hospitalization costs [ 2 ]. Although the exact molecular mechanism of KD vasculitis still remains obscure, clinical and experimental evidence has shown that KD vasculitis is closely associated with increased vascular permeability that leads to vascular leakiness, decreased plasma proteins, and inflammatory cell infiltration of endothelium [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation of ECs is closely associated with the onset and progression of KD and its complication—CALs, which has not been fully illustrated [ 25 ]. Here, we identified a novel Sema4D-plexin B axis-mediated proinflammatory cytokine production mechanism of ECs and highlighted the pathological involvement of Sema4D in KD-CALs.…”
Section: Discussionmentioning
confidence: 99%
“…Papers with the keyword "coronary artery diseases" (CAD) researched regulators in patients with Kawasaki disease [31] and rheumatoid arthritis [32]. In addition, they studied the use of 18F-fluorodeoxyglucose positron emission tomography imaging [33] for identifying CAD and biomarker proprotein convertase subtilisin/kexin type-9 [34] for predicting CAD.…”
Section: Purple Cluster (Part 2)mentioning
confidence: 99%